Sushi King AEON Shah Alam / Ammar Yasier Azman … [et al.] - AZMAN, AMMAR YASIER; ADZAMEE, MOHAMEDARIEF; ABDUL HAMID, MUHAMMAD AMIR; MOHD AZLI, MUHAMMAD SYAHMI IZZAT; UNGKU ABDUL RAHMAN, UNGKU MOHAMED ISMAIL ADRIAN (2019)
Sushi King Sdn. Bhd. is a Japanese restaurant that serves Japanese cuisine in Malaysia. Sushi King was established in 1995, Sushi King's product was first introduced as a sushi on the kaiten or revolving sushi with quick-service restaurant concept. Sushi King has evolved from a single outlet in Kuala Lumpur to a well-known brand with over 100 restaurants nationwide and become the largest sushi chain restaurant in the country. Sushi King Sdn.Bhd. is a member of the Texchem Group Company, is one of the subsidiaries under Texchem Resources Bhd (Texchem).